Weight cycling in combat sports: revisiting 25 years of scientific evidence - Lakicevic, N.; Mani, D.; Paoli, A.; Roklicer, R.; Bianco, A.; Drid, P. (BMC Sports Science, Medicine and Rehabilitation, 2021)
Background As combat sports are classified by body mass, many athletes engage in rapid weight loss (RWL) prior to competition so they can gain an advantage over lighter opponents. Following the weigh-in, athletes engage in rapid weight gain (RWG), whereby some athletes have been able to compete up to three weight categories greater than the official division weighed in at.